1984
DOI: 10.1111/j.1365-2141.1984.tb02899.x
|View full text |Cite
|
Sign up to set email alerts
|

Low dose cytosine arabinoside: partial remission of acute myeloid leukaemia without evidence of differentiation induction

Abstract: Thirteen patients with acute myeloid leukaemia aged from 19 to 81 were treated with low dose cytosine arabinoside (ARA-C) in a dose of 10-15 mg/m2 twice daily subcutaneously. Three complete remissions were obtained. Partial responses were observed in a further two patients. To analyse the action of low dose ARA-C freshly isolated leukaemic cells and cells from the cloned promyelocytic leukaemia cell line (HL60) were cultured in vitro in the presence of cytosine arabinoside. Minimal evidence of differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Most experimen tal evidence indicates an inhibition of the DNA-synthesis [10][11][12][13]; however, it has been suggested that low-dose ARA-C provides a differentiation of the im mature leukaemic cells [3][4][5]14]. The fact that we saw 2 complete remissions in patients who had not ob tained remissions after 2 courses of aggressive combi nation chemotherapy might speak in favour of the lat ter concept.…”
Section: Discussionmentioning
confidence: 80%
“…Most experimen tal evidence indicates an inhibition of the DNA-synthesis [10][11][12][13]; however, it has been suggested that low-dose ARA-C provides a differentiation of the im mature leukaemic cells [3][4][5]14]. The fact that we saw 2 complete remissions in patients who had not ob tained remissions after 2 courses of aggressive combi nation chemotherapy might speak in favour of the lat ter concept.…”
Section: Discussionmentioning
confidence: 80%
“…Its mechanism of action at low doses is not completely clear: Some believe that it retains cytotoxic action, and some have view that it induces apoptosis by differentiation induction. 12,13 There is also a perception that LD ara-C induces excess cytopenia, thereby defeating the objectively of being optimally tolerable to the older patient. An alternative and widely used approach is to provide best supportive care, which includes blood product support and antibiotic treatment, as required with periodic treatment with hydroxyurea (HU) to control the peripheral white blood count.…”
mentioning
confidence: 99%
“…These authors included histone deacetylase inhibitors, such as valproic acid, which have a proven efficient to overcome differentiation arrest of AML blasts 12 . We decided to use this regimen because of its response rates.…”
Section: Discussionmentioning
confidence: 99%